THE RELATIONSHIP BETWEEN BOARD DIVERSITY AND PERFORMANCE: EVIDENCE FROM MALAYSIA PUBLIC LISTED COMPANIES - Syaiful Baharee Jaafar (International Journal of Accounting, Finance and Business, 2020)
Being on a board of directors is a responsibility to improve performance by leading the company through the present types of board diversity and to bring a variety of ideas, strategies and planning to address different market issues. The market is complex because it consists of people from different backgrounds, with different behaviors, of different genders, age, and others demographics. Therefore, board diversity is necessary to understand the changing market and technology. To understand the market and improve the performance, the present of board diversity is very important. Based on a sample size of 374 firms listed in Bursa Malaysia, with 674 pieces of panel data from 2015 and 2016, this study finds the significance of the relationship between gender, diversity and firm performance. Further analysis finds no evidence that age diversity influences a firm’s performance.